The trust broker game: A three-player trust game with probabilistic returns and information asymmetry - Anirudh Tagat; Hansika Kapoor (Kiel Institute for the World Economy (IfW), 2017)
This paper experimentally investigates trust and trustworthiness in a repeated and sequential three-player trust game with probabilistic returns and information asymmetry. It adds to the existing literature by combining experimental features from recent work in the trust game. The authors use random variations in the multiplier value, a third player without an initial endowment, undisclosed termination rules, and variations in information availability related to transactions. The framework is novel in that the game continues even if the first player transfers no amount to the second player. Using participants from India, the results are broadly consistent with past evidence on the trust game. All players are more trusting when information of their transfers and earnings are made available to other players. The third player (termed the "trust broker") transfers a larger amount when information on transfers is disclosed to other players. The authors find that information availability leads to a significant increase in the trust broker's reciprocity, as defined by the amount that is returned to Player 2. Social desirability, cultural contexts, and learning effects are discussed in terms of scope for future research.
http://dx.doi.org/10.7910/DVN/XB9ACC
Keywords: C91; C92; D64; D70; 330; trust game; multi-level games; uncertainty; trustworthiness; selfishness; reciprocity